FIELD PERFORMANCE OF HOT IN-PLANT PRODUCED ASPHALTIC CONCRETE WEARING COURSE (ACWC) WITH 30% RECLAIMED ASPHALT PAVEMENT (RAP) (Jurnal Teknologi (Sciences & Engineering), 2024)
Hot in-plant recycling stands as an effective yet underutilized method in Malaysia for reusing pavement milling waste, resulting in insufficient established benchmarks and validated trials.  The Utilization of Reclaimed Asphalt Pavement (RAP) can divert a significant amount of waste asphalt millings from landfills, while conserving energy and natural resources. This study focused on the recycled mixture, ACWC-30RAP, which integrated 30% Reclaimed Asphalt Pavement (RAP). In July 2022, a 400 m trial lay was conducted from KM413.90 to KM414.30 Southbound (SB), Section C3, along the PLUS North-South Expressway (NSE).  Field tests were systematically conducted on both the ACWC-30RAP and conventional ACWC20 mixtures at different phases including month-6, month-9, and month-12 post-construction. The primary objective was to assess fundamental properties related to the structural stiffness of pavement layers as well as the pavement performance and condition for both trial sections using various field testing including Falling Weight Deflectometer (FWD) and Multi-Laser Profiler (MLP).  Following the 12-month trial period, both the ACWC-30RAP and conventional ACWC20 mixtures experienced actual traffic loading and environmental conditions. Remarkably, the ACWC-30RAP demonstrated comparable field performance as the conventional ACWC20. This alignment in performance signified a promising avenue for employing the recycled mixture with high RAP content. Using ACWC-30RAP can also provide economic benefit, reducing the production cost by approximately 25%. In essence, the ACWC-30RAP had achieved an equivalent level of confidence to the conventional ACWC20 mixture, which was exclusively composed of virgin materials. cts.